Clinical and epidemiological characteristics of patients with early syphilis from three academic centres in Poland, Germany and Ireland: initial findings from the POETS study. (5th March 2015) - Rowley, D; Swięcki, P; Firlag-Burkacka, E; Sabin, C; Kümmerle, T; Surah, S; Sadlier, C; O'Dea, S; Horban, A; Fätkenheuer, G; Mulcahy, F
Abstract : Objectives: Syphilis recognition in HIV-positive patients has important implications. Initial data from this study, established in June 2012 to better understand the natural history of syphilis and treatment response, examine the characteristics of patients including sexual behaviour, rates of concurrent sexually transmitted infections (STI) and type of treatment given. Methods: Patients were recruited from Ireland, Poland and Germany. Data gathered included demographics, method of syphilis acquisition, stage of syphilis infection, HIV status, nadir and current CD4 counts and HIV viral suppression rates. Data were then subanalysed into HIV-positive and HIV-negative groups. Results: Of 175 patients recruited, 68% were HIV-positive and 86.3% were men who have sex with men. Most HIV-positive patients presented with secondary syphilis (55.7% vs 13.2%) (p=0.0001) while the majority of HIV-negative patients had primary syphilis noted at the time of recruitment (47.2% vs18.9%, p=0.0002). Approximately half of all patients had a HIV RNA viral load <40 copies/mL (55%). Previous syphilis infection occurred more frequently in HIV-positive than HIV-negative patients (p=0.0001). Concurrent STIs at the time of syphilis diagnosis were found in 26.8%, of whom 31 (25.4%) were HIV-positive (p=0.64). HIV-positive patients received doxycycline more frequently than their HIV-negative counterparts (33.6% vs 1.9%, p=0.0001) while HIV-negative patients were treated with long-acting penicillin in 88.7% of cases vs 58% of HIV-positive patients (p=0.0002). Conclusions: A 40% rate of unsuppressed viraemia, high levels of STIs and varying treatment regimens represent a public health risk for Europe, suggesting the model of sexual healthcare delivery in HIV-positive patients requires further evaluation.